Reliability and validity of the self-reported frailty screening questionnaire in older adults - Yanhong Zhang; Yaxin Zhang; Yun Li; Piu Chan; Lina Ma (SAGE Publishing, 2020)
Background: Frailty is one of the most important risk factors for adverse outcomes in older adults. Despite a high prevalence, there is still a lack of frailty screening instruments specific to Chinese older adults. We developed a simple frailty screening questionnaire (FSQ) that could predict long-term mortality. We aimed to explore the reliability and construct validity of this new measurement tool. Methods: A total of 205 individuals aged 65 years or older were recruited in this study. The FSQ and frailty phenotype were assessed. The FSQ included self-reported slowness, weakness, weight loss, inactivity, and exhaustion. A subgroup of 109 participants completed the FSQ a second time 2 weeks later for test-retest reliability. Frailty phenotype included slowness, exhaustion, weight loss, weakness, and inactivity. Results: The intraclass correlation coefficient for the FSQ, slowness, weakness, weight loss, inactivity and exhaustion were 0.937, 0.938, 0.934, 0.921, 0.826, and 0.832, respectively. Using a cut-off of 3, the sensitivity, specificity, and area under the curve of the receiver operating characteristic were 52.6%, 93.5%, and 0.883 ( p  < 0.001), respectively. The kappa coefficient between the FSQ and frailty phenotype was 0.431 ( p  < 0.001). FSQ score was negatively correlated with walking speed and grip strength, and positively correlated with age. Frailty defined by the FSQ was associated with older age, chronic diseases, and worse physical function. Conclusions: The FSQ is a potentially useful, reliable, and valid instrument in screening frailty in older adults, and can be recommended to identify frailty in clinical settings.